Hindī Rāma-kāvya meṃ svabhāvokti, San 1450 se 1650 Ī. taka - Bhāradvāja, Kauśalyā, 1945- (Manthana, 1982)
Study of a type of figure of speech (svabhāvokti) in the medieval Hindi poetry on Rāma, Hindu deity.